La motivación de la belleza - Ortega del Rincón, Tomás; Ortega Cubero, Inés; Ortega Cubero, Elena; Crespo Crespo, Cecilia (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2005)
La motivación de la belleza